Brand preference in Islamic banking - Mohd. Israil, Khaliq Ahmad; Mohd. Rustam, Ghulam Ali; Michael, M. Dent (Emerald Publishing Group, 2011)
Previous literature suggests that factors such as banks’ strong Islamic reputation as well as better financial and banking services are to be among the leading factors in the selection of the respective Islamic bank. The aim of this study would be to examine the bank selection criteria being employed by students in Malaysia. This empirical study will consists of approx. 300 respondents of the International Islamic University Malaysia, main campus will serve as a sample for the study. The choice of younger customer would reflect the future potential market for Islamic banking marketing services whose average age would be between 19 to 25 years. Our empirical study would be relied on 5 selection factors extracted from relevant literature, personal experience and interviews with some bank officials and college students. This study may be also designed to examine this young group of customers’ knowledge of Islamic banking and the factors to be considered in the process of selecting an Islamic bank would be by demographic group and socio-economic characteristics. The data so collected from the study will be analysed by SPSS Program, mean factor analysis and then factor analysis to enhance the quality of the empirical survey. The main implication of this study is to help marketing executives in the Islamic banks to plan better marketing strategies that would attract new customers as well as retain the existing ones, given the high competitive environment dominating the financial industry.